Right hemitruncus in adulthood: an unusual finding - Huerta Robles, Rocío (2020)
Hemitruncus arteriosus is a rare congenital heart disease characterized by the abnormal origin of one of the branches of the pulmonary artery from the ascending aorta. In most cases, its diagnosis is made during childhood; in addition, due to its high morbidity and mortality, its asymptomatic evolution and survival to adulthood is extremely unusual. We present the case of a 30-year-old male patient, with a history of surgical closure of patent ductus arteriosus during childhood, who was asymptomatic until a year ago, in whom hemitruncus arteriosus was diagnosed after recurrent episodes of hemoptysis.